PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN PRODUKTIF TKJ DI SMK WIDYAGAMA MALANG - Fahmi Efendi Yusuf; Waras Kamdi; Syaad Patmanthara (Pascasarjana Universitas Negeri Malang, 2016)
Information technology is useful only as a medium of information is a very important role in the search for information, it is inversely proportional to that existing in SMK Widyagama unfortunate, especially on the issue of learning is carried out with conventional methods that teachers simply do meaningful assisted power point lecture. Presentations used are limited to static media, so as to the concept of data flow on the network is less understood by the students, while the students-students of SMK Widyagama Malang at this point is equipped with TAB Android. To overcome these limitations, the LAN-based learning media is used interactive multimedia as teaching aids in learning. To produce the product development. research test media experts, subject matter experts and students - Students of SMK Widyagama Malang.The results empirically development in the form of web multimedia interactive teaching competence of the human respiratory system. The products have been validated and fit for use as an alternative medium of interactive learning at school TKJ, with the results of the validation of media experts on average by 85.2%, materials experts give an average value of 99.1%, and 93.1 students validation results. Teknologi informasi bermanfaathanya sebagai media informasi yang sangat berperan penting dalam mencari informasi, hal ini berbanding terbalik dengan yang ada di SMK Widyagama malang, terutama pada masalah pembelajaran masih dilaksanakan dengan metode konvensional yakni guru hanya melakukan ceramah berbantuan power point. Presentasi yang digunakan masih sebatas media statis, sehingga untuk konsep aliran data pada jaringan kurang bisa dipahami oleh siswa, sedangkan para siswa-siswi SMK Widyagama Malang pada saat ini  sudah dibekali TAB Android. Untuk mengatasi keterbatasan tersebut maka digunakanlah media pembelajaran LAN berbasis multimedia interaktif sebagai media bantu dalam pembelajaran. Untuk menghasilkan produk pengembangan ini penelitian melakukan uji coba pada macam macam validator, antara lain ahli media, ahli materi dan siswa-siswi SMK Widyagama Malang. Hasil penelitia pengembangan berupa web multimedia pembelajaran  interaktif  kompetensi mata pelajaran produktif TKJ (Teknik Komputer Jaringan). Produk  telah  divalidasi  dan  layak  digunakan  sebagai  salah  satu alternatif  media  pembelajaran  interaktif TKJ di  sekolah,  dengan  hasil validasi  dari   ahli   media  rata-rata  sebesar   85,2%,  ahli  materi memberikan nilai  rata-rata sebesar 99,1%, dan   hasil validasi siswa 93.1%.